Rational Design of Phe‐BODIPY Amino Acids as Fluorogenic Building Blocks for Peptide‐Based Detection of Urinary Tract Candida Infections. Issue 17 (26th February 2022) - Mendive‐Tapia, Lorena; Mendive‐Tapia, David; Zhao, Can; Gordon, Doireann; Benson, Sam; Bromley, Michael J.; Wang, Wei; Wu, Jun; Kopp, Adelina; Ackermann, Lutz; Vendrell, Marc
Abstract: Fungal infections caused by Candida species are among the most prevalent in hospitalized patients. However, current methods for the detection of Candida fungal cells in clinical samples rely on time‐consuming assays that hamper rapid and reliable diagnosis. Herein, we describe the rational development of new Phe‐BODIPY amino acids as small fluorogenic building blocks and their application to generate fluorescent antimicrobial peptides for rapid labelling of Candida cells in urine. We have used computational methods to analyse the fluorogenic behaviour of BODIPY‐substituted aromatic amino acids and performed bioactivity and confocal microscopy experiments in different strains to confirm the utility and versatility of peptides incorporating Phe‐BODIPYs. Finally, we have designed a simple and sensitive fluorescence‐based assay for the detection of Candida albicans in human urine samples. Abstract : The rational design and synthesis of the first fluorogenic Phe‐based BODIPY amino acids, and their application to produce peptide‐based agents for rapid and wash‐free labelling of fungal cells is described. This technology has been exploited to develop a sensitive and low‐cost fluorescence‐based assay for the detection of Candida albicans in human urine using simple benchtop spectrophotometers.